Dinitrosopiperazine-Mediated Phosphorylated-Proteins Are Involved in Nasopharyngeal Carcinoma Metastasis - Tan, Gongjun (Int J Mol Sci, 2014)
N,N'-dinitrosopiperazine (DNP) with organ specificity for nasopharyngeal epithelium, is involved in nasopharyngeal carcinoma (NPC) metastasis, though its mechanism is unclear. To reveal the pathogenesis of DNP-induced metastasis, immunoprecipitation was used to identify DNP-mediated phosphoproteins. DNP-mediated NPC cell line (6-10B) motility and invasion was confirmed. Twenty-six phosphoproteins were increased at least 1.5-fold following DNP exposure. Changes in the expression levels of selected phosphoproteins were verified by Western-blotting analysis. DNP treatment altered the phosphorylation of ezrin (threonine 567), vimentin (serine 55), stathmin (serine 25) and STAT3 (serine 727). Furthermore, it was shown that DNP-dependent metastasis is mediated in part through ezrin at threonine 567, as DNP-mediated metastasis was decreased when threonine 567 of ezrin was mutated. Strikingly, NPC metastatic tumors exhibited a higher expression of phosphorylated-ezrin at threonine 567 than the primary tumors. These findings provide novel insight into DNP-induced NPC metastasis and may contribute to a better understanding of the metastatic mechanisms of NPC tumors.